Effect of electroconvulsive seizures on cognitive flexibility. Issue 7 (7th March 2016) - Svensson, Maria; Grahm, Matilda; Ekstrand, Joakim; Höglund, Peter; Johansson, Mikael; Tingström, Anders
ABSTRACT: Electroconvulsive seizures (ECS), an animal model of electroconvulsive therapy, strongly stimulate hippocampal neurogenesis, but it is not known how this relates to the therapeutic effect or to the unwanted cognitive side effects. Recent findings suggest that neurogenesis might be important for flexible learning in changing environments. We hypothesize that animals receiving ECS treatment, which induces hippocampal neurogenesis, will show enhanced cognitive flexibility compared with controls. We have utilized a touch screen‐based cognitive test (location discrimination (LD) task) to assess how five consecutive ECS treatments affect cognitive flexibility (measured as reversal of cognitive strategy) as well as spatial pattern separation ability. ECS‐treated animals performed more reversals in the LD task earlier than controls over the 9 experimental weeks irrespective of spatial separation of visual stimuli, indicating an enhanced cognitive flexibility but unaffected pattern separation ability after ECS. We observed no correlation between hippocampal neurogenesis and the number of performed reversals during the last experimental week. This is the first study to elucidate the effect of ECS on cognitive flexibility. Our results indicate that ECS improves cognitive flexibility without affecting spatial pattern separation ability. Whether cognitive flexibility is enhanced via neurogenesis or other ECS‐modulated processes, remains unknown. © 2016 Wiley Periodicals, Inc.